(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: (1) To describe the CAUTI prevention care bundle implemented in the Department of General Surgery, Transport Hospital; and (2) to evaluate implementation outcomes at the unit level. Methods: A cross-sectional descriptive study was conducted among 68 catheterized patients from May to July 2024. The four-component care bundle was implemented in accordance with guidance from the CDC, AHRQ, and the Ministry of Health (Viet Nam). Monitored indicators included timely catheter removal (within 24 hours), nurses’ knowledge and practice scores, urinary tract infection status, length of hospital stay, and patient satisfaction. Results: Overall, 85.3% of patients had their urinary catheters removed within the first 24 hours. No urinary tract infections were recorded at discharge. Nurses’ practice scores exceeded knowledge scores (8.8/10 vs. 7.2/10). The mean length of stay was 5.7 ± 1.1 days. Patient satisfaction with care and counseling was 94%. Conclusions: The CAUTI prevention care bundle was feasible and effective in reducing infection risk and improving quality of care. Continued implementation, rigorous monitoring, and scale-up to other high-risk units are recommended.